American College of Rheumatology/European League Against Rheumatism Provisional Definition of Remission in Rheumatoid Arthritis for Clinical Trials. Issue 3 (3rd February 2011) - Felson, David T; Smolen, Josef S; Wells, George; Zhang, Bin; van Tuyl, Lilian H D; Funovits, Julia; Aletaha, Daniel; Allaart, Cornelia F; Bathon, Joan; Bombardieri, Stefano; Brooks, Peter; Brown, Andrew; et al.
Abstract : Objective: Remission in rheumatoid arthritis (RA) is an increasingly attainable goal, but there is no widely used definition of remission that is stringent but achievable and could be applied uniformly as an outcome measure in clinical trials. This work was undertaken to develop such a definition. Methods: A committee consisting of members of the American College of Rheumatology, the European League Against Rheumatism, and the Outcome Measures in Rheumatology Initiative met to guide the process and review prespecified analyses from RA clinical trials. The committee requested a stringent definition (little, if any, active disease) and decided to use core set measures including, as a minimum, joint counts and levels of an acute-phase reactant to define remission. Members were surveyed to select the level of each core set measure that would be consistent with remission. Candidate definitions of remission were tested, including those that constituted a number of individual measures of remission (Boolean approach) as well as definitions using disease activity indexes. To select a definition of remission, trial data were analysed to examine the added contribution of patient-reported outcomes and the ability of candidate measures to predict later good radiographic and functional outcomes. Results: Survey results for the definition of remission suggested indexes at published thresholds and a count of core set measures, with each measure scored as 1 or less (eg, tender and swollen joint counts, C reactive protein (CRP) level, and global assessments on a 0–10 scale). Analyses suggested the need to include a patient-reported measure. Examination of 2-year follow-up data suggested that many candidate definitions performed comparably in terms of predicting later good radiographic and functional outcomes, although 28-joint Disease Activity Score–based measures of remission did not predict good radiographic outcomes as well as the other candidate definitions did. Given these and other considerations, we propose that a patient's RA can be defined as being in remission based on one of two definitions: (1) when scores on the tender joint count, swollen joint count, CRP (in mg/dl), and patient global assessment (0–10 scale) are all ≤1, or (2) when the score on the Simplified Disease Activity Index is ≤3.3. Conclusion: We propose two new definitions of remission, both of which can be uniformly applied and widely used in RA clinical trials. The authors recommend that one of these be selected as an outcome measure in each trial and that the results on both be reported for each trial.